Generalized nilpotent braces and nilpotent groups - Martyn Dixon; Leonid Kurdachenko; Igor Subbotin (International Journal of Group Theory)
The authors give a brief survey of some results concerning nilpotent braces and their generalizations. Various results concerning $\star$-hypercentral and locally $\star$-nilpotent braces are given.